The Influence of Digital Leadership, Knowledge Management Capability and Innovation Climate on Digital Innovation Capability in Digital-Based MSMEs - Afiat, Dominica Dini; Setiono, Agus; Putranto, Samuel Aditya Eko; Sugiarti; Setyawasih, Rianti; Nurdiansyah, Yanuar (Journal of Information System, Technology and Engineering, 2026)
The digital economic transformation needs digital MSMEs to create sustainable innovation capabilities which will help them succeed in their business competition. The study investigates how digital leadership and knowledge management capability together with innovation climate evaluation affect the digital innovation capacity of digital-based MSMEs. The researchers executed their research through a quantitative research method which used an explanatory research design for their study. The study collected data by surveying digital-based MSME owners and managers who participated through purposive sampling. The researchers used multiple linear regression to analyze the data after completing validity and reliability testing and classical assumption testing. The research established that digital leadership and knowledge management capability with innovation climate create a positive connection which improves digital innovation capacity. Digital leadership functions as an organizational power that propels digital transformation while knowledge management capability allows organizations to gather new information and apply their existing knowledge and innovation climate establishes a workspace that fosters innovation activities. The research findings offer MSME managers strategic guidance which helps them create policies that enable sustainable technology-based innovation.